UMP honours staff, celebrates fellows completing studies - UMP, PNC (2019)
Eighteen years’ experience as a staff member at Universiti Teknologi Malaysia (UTM) which later changed their name to Kolej Universiti Teknologi dan Kejuruteraan Malaysia (KUKTEM) and Universiti Malaysia Pahang (UMP) was truly memorable for Nor Ashikin Abul Aziz who has now completed her service as a lecturer at the Centre for Modern Languages and retired at the age of 60 on 3 October 2019.